The Palgrave Handbook of Women and Science since 1660
XXVIII, 658 p. 28 illus., 12 illus. in color.
Keywords: This handbook provides a comprehensive overview of core areas of investigation and theory relating to the history of women and science. Bringing together new research with syntheses of pivotal scholarship, the volume acknowledges and integrates history, theory and practice across a range of disciplines and periods. While the handbook’s primary focus is on women's experiences, chapters also reflect more broadly on gender, including issues of femininity and masculinity as related to scientific practice and representation. Spanning the period from the birth of modern science in the late seventeenth century to current challenges facing women in STEM, it takes a thematic and comparative approach to unpack the central issues relating to women in science across different regions and cultures. Topics covered include scientific networks; institutions and archives; cultures of science; science communication; and access and diversity. With its breadth of coverage, this handbook will be the go-to resource for undergraduates taking courses on the history and philosophy of science and gender history, while at the same time providing the foundation for more advanced scholars to undertake further historical and theoretical investigation.